Currarino syndrome masquerading as recurrent pre-sacral abscess - Vineet Aggarwal; Neeti Aggarwal; Rohit Bhoil; Vijay Kumar; Neeraj Kumar; Surya P. Singh; Mansi Verma (The Egyptian Journal of Radiology and Nuclear Medicine, 2017)
Background: Currarino recognized a triad of congenital malformations of the hindgut and the sacrococcygeal spine as a distinct syndrome. A characteristic radiological sign described as scimitar sacrum is pathognomonic of the syndrome. A radiograph of the pelvis requested for some other reason may detect the typical scimitar detect in the lower sacrum and the coccyx. Case: We report a case of a ten year old girl with recurrent pre-sacral abscess in whom the diagnosis of Currarino syndrome was suspected on plain radiography and confirmed on CT/MRI. To the best of our knowledge this is the second case of Currarino Syndrome being diagnosed in a patient following presentation as a presacral abscess. Conclusion: The clinical features, unique radiologic appearance, and importance of a correct diagnosis of the Currarino triad are discussed which often requires inter-departmental cooperation for correct diagnosis and management.